"Aesthetics of Contrast in Al-Rafei's book Wahi Al-Qalam" (Raparin Journal of Humanities (RJH), 2019)
Mustafa Sadiq Al-Rafei is one of the renaissance writers and a famous essay writer who defends his poor people with his essays. This paper (Systematic Contradiction in Al-Rafei Essays) is a study of Al-Rafei’s book Wahi Al-Qalam which consists of three chapters with more than a thousand pages. It demonstrates his ingenuity of using systematic contradiction along with his artistic ability in adapting intellectual heritage and language in his essays, as well as showing a vast knowledge in his mother language and his people’s heritage which make him to be creative rhetorically through adding some aesthetics and rhythm to his texts for grabbing reader’s attention and making them aware of the author’s intentions.This study consists of an introduction and three chapters, while the introduction is about arrangement and contradiction. The first chapter studies contrast (Complementary and multiple antonym) and negative statements. Second chapter is dealing with contradiction in which two or more combined words are opposite to another two or combined more words while the individual words are opposite too, and it demonstrates both aspects, complementary and contextual. The third chapter studies another type which scientists and pioneers have not tried, and that can be called textual opposites that go beyond lexical, phrases, or clauses to focus on text to text contradiction throughout its conflicts and contradiction of characters.And finally, the study is provided with an abstract in both Kurdish and English languages along with the reference list.